2020
DOI: 10.1093/mnras/staa2833
|View full text |Cite
|
Sign up to set email alerts
|

Star formation in CALIFA survey perturbed galaxies – I. Effects of tidal interactions

Abstract: We explore the effects of tidal interactions on star formation (SF) by analysing a sample of CALIFA survey galaxies. The sample consists of tidally and non-tidally perturbed galaxies, paired at the closest stellar mass densities for the same galaxy type between subsamples. They are then compared, both on the resolved Star Formation Main Sequence (SFMS) plane and in annular property profiles. Star-forming regions in tidally perturbed galaxies exhibit flatter SFMS slopes compared to star-forming regions in non-t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 109 publications
0
2
1
Order By: Relevance
“…We find a bimodality -two peaks in the distribution of spaxels in the mass-metallicity space for galaxy pairs -a feature that is not present in the MaNGA sample as a whole. This bimodality was not observed in the study by Morales-Vargas et al (2020), a previous spatially resolved study on perturbed galaxies. 2.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…We find a bimodality -two peaks in the distribution of spaxels in the mass-metallicity space for galaxy pairs -a feature that is not present in the MaNGA sample as a whole. This bimodality was not observed in the study by Morales-Vargas et al (2020), a previous spatially resolved study on perturbed galaxies. 2.…”
Section: Discussioncontrasting
confidence: 56%
“…2 show that while some spaxels in galaxy pairs show a dilution in gas phase metallicity, which is in agreement with the above-mentioned works that investigate the MZR for galaxy pairs, there are also spaxels that do not show diluted metallicities. This bimodality in distribution is not present in Morales-Vargas et al (2020). We looked to see if there were any properties that may show a close relation with the loci of the spaxels.…”
Section: Discussionmentioning
confidence: 96%
“…Whether and when the global SFR, the central SFR, and the SFR in the outer disks are boosted or quenched are key signatures that are frequently searched for. It was found that mergers or galactic interactions on average moderately and significantly elevate the total and central SFR of star-forming galaxies (e.g., Mihos & Hernquist 1994;Lisenfeld et al 2007;Morales-Vargas et al 2020; but see Martinez-Badenes et al 2012 for the case in compact groups). The central and total SFR of the primary galaxy (the more massive one) is more strongly elevated if the interacting pair has higher SFR, higher stellar mass, smaller separation, or lower relative velocity (e.g., Zasov & Sulentic 1994;Alonso et al 2004;Bustamante et al 2018).…”
Section: Introductionmentioning
confidence: 99%